Options for studying human motion: neurophysiological program sLORETA - Dominika Dvořáčková; David Pánek; Dagmar Pavlů (Karolinum Press, 2019)
Evaluation of motions is the basis for the diagnosis of human locomotor system disorders. Analyses are usually focused on the performance components of this system, i.e. on the skeleton and muscles. However, where comprehensive diagnosis is to be obtained, the motor system must be evaluated as a whole, without omitting any of its parts. So, evaluation of the control function is very important to body motion evaluation. The method that is normally used to evaluate the activity of brain is electroencephalography, which is superior to other brain activity-evaluating methods in many respects. However, EEG has also a major drawback, namely, it cannot precisely locate the activated and deactivated brain regions. This drawback can be avoided by using the sLORETA neurophysiological program, a tool that can transform EEG data to 3D brain images and finding application across a wide range of clinical branches of medicine - neurology, neurophysiology, psychiatry, physiotherapy and also in sports.